An economic analysis of varicella immunization in the Singapore military. Issue 1 (December 2016) - Goh, Jake; Ho, Marc; Koh, W.; Lee, Vernon
Abstract Background Varicella outbreaks occur frequently in closed environments such as those of militaries. This paper compares the economic outcomes of varicella vaccination in enlisted servicemen without prior reported varicella infection or vaccination. Methods We analyzed the economic outcomes of a varicella vaccination program on all enlisted servicemen without prior reported varicella infection or vaccination in the Singapore Armed Forces (SAF) between December 11, 2010 – December 20, 2013, compared with the previous program of varicella vaccination only for selected personnel between December 1, 2007 – December 10, 2010. Results In the at-risk population of all active SAF servicemen, the program of varicella vaccination for all servicemen without prior reported varicella infection or vaccination upon enlistment would save 72.0 work days per 1000 (95 % CI: 61.2 - 82.9), valued at SG$6, 544 per 1000 (95 % CI: 6, 524 - 6, 564), i.e., costing SG$91.5 per work day saved (95 % CI: 78.7 - 107.3). This also results in a reduction of 2.7 varicella cases per 1000 and 5.43 outbreaks per 10000, or a total savings of SG$1, 695 per 1000 (95 % CI: −2, 730 - 6, 834), taking into account the cost of work days lost over a three-year period, compared with the previous regime of vaccinations only for selected individuals. Conclusion The varicella vaccination strategy targeting all enlisted servicemen without prior reported varicella infection or vaccination is able to prevent varicella infections and outbreaks, thus reducing absenteeism and days lost.